Gambaran Kepribadian Hardiness Atlet Paralympic Atletik Lari Cepat - Kinanthi, Gretty Wida; Jannah, Miftakhul (Jurnal Psikologi Teori dan Terapan, 2016)
This research was motivated by a phenomenon of paralympic athletes with physical, visual, hearing and intellectual dissabilities that were demanded to keep confident and overcome problems. Stress often happens to athletes when the match is in progress so this stress causes failure on their competition and they are demanded to come up again after failure. Athletes need a tendency of hardiness personality to overcome every problem in the match so the atheletes can gain an achievement. The purpose of this research was to describe a paralympic athleteâs tendency of hardiness personality. This research used qualitative research with case-study method. A paralympic athelete who had international achievement in 200 and 400-meter sprints was recruited as the participant in this research. Data were collected using interviews, observations and document reviews which then analyzed by using thematic analysis. The results showed that the participant had tendency of hardiness personality shown by his understanding of the purpose of life, involving his self in daily activities, and controlling each of his problem. The participant also had optimism and ready to take the challenge.Â Abstrak: Penelitian ini dilatarbelakangi oleh fenomena atlet paralympic dengan ketidakmampuan secara fisik, penglihatan, pendengaran dan intelektual yang dituntut untuk tetap percaya diri dan mampu mengatasi permasalahan. Stres seringkali terjadi pada atlet ketika pertandingan berlangsung sehingga stres ini menyebabkan kegagalan dipertandingannya dan mereka dituntut untuk bangkit kembali setelah kegagalan. Atlet membutuhkan kecenderungan kepribadian hardiness untuk mengatasi setiap masalah dalam pertandingan sehingga atlet dapat mencapai prestasi. Tujuan penelitian ini adalah untuk menggambarkan kecenderungan kepribadian hardiness atlet paralympic. Penelitian ini menggunakan penelitian kualitatif dengan metode studi kasus. Atlet paralympic yang memiliki prestasi tingkat internasional nomor perlombaan lari cepat 200 dan 400 meter dipilih sebagai partisipan pada penelitian ini. Data dikumpulkan dengan wawancara, observasi dan dokumentasi. Hasil menunjukkan bahwa partisipan memiliki kecenderungan kepribadian hardiness yang ditunjukkan dengan pemahamannya pada tujuan hidup, melibatkan diri dalam aktivitas sehari-hari, pengendalian setiap masalah. Partisipan juga memiliki optimis dan berani mengambil tantangan.